2005
DOI: 10.1211/jpp.57.11.0014
|View full text |Cite
|
Sign up to set email alerts
|

Statin-induced apoptosis linked with membrane farnesylated Ras small G protein depletion, rather than geranylated Rho protein

Abstract: Rhabdomyolysis is a severe adverse effect of 3-hydroxy-3-methylglutaryl-coenzyme A reductase inhibitors (statins). This myopathy is strongly enhanced by the combination with statins and fibrates, another hypolipidaemic agent. We have evaluated the initial step of statin-induced apoptosis by the detection of membrane flip-flop using flow cytometric analysis. L6 rat myoblasts were treated with various statins (atorvastatin (3 microM), cerivastatin (3 microM), fluvastatin (3 microM), pravastatin (3 mM), or simvas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 26 publications
1
50
1
Order By: Relevance
“…2). One group using rat immortalized L6 myoblasts reported that the depletion of FPP is critical for myotoxicity (22), but another laboratory using the same cell line suggested that GGPP was the critical isoprenoid (12). In our hands, it was not FPP (3 mM), but GGPP (3 mM) alone, because the addition of GGPP, not FPP, in the presence of fluvastatin completely canceled the toxic effects of statins in skeletal myofibers (15,17).…”
Section: Depletion Of Geranylgeranylpyrophosphate Triggers Statin Myomentioning
confidence: 60%
“…2). One group using rat immortalized L6 myoblasts reported that the depletion of FPP is critical for myotoxicity (22), but another laboratory using the same cell line suggested that GGPP was the critical isoprenoid (12). In our hands, it was not FPP (3 mM), but GGPP (3 mM) alone, because the addition of GGPP, not FPP, in the presence of fluvastatin completely canceled the toxic effects of statins in skeletal myofibers (15,17).…”
Section: Depletion Of Geranylgeranylpyrophosphate Triggers Statin Myomentioning
confidence: 60%
“…Contrary to this effect, we observed ras immunoreactivity was decreased 72 h after treatment with low concentrations of MMC. This could be attributed to depletion of the protein synthesis capacity in T24 cells after 72 h [29] . These data suggest that ras siRNA would be most effective 72 h after treatment with low concentrations of MMC.…”
Section: Discussionmentioning
confidence: 99%
“…4,19,20) These isoprenoids are used for the prenylation of ras and rho GTPases, which are involved in signal transduction, and therefore, their lack of signal transduction causes severe cell dysfunction. We have previously studied the action mechanism of statin-induced rhabdomyolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Additional study revealed that apoptosis was induced by dropping ras GTPase from the cell membrane, indicating that the depletion of farnesyl pyrophosphate was essential for statin-induced apoptosis. 4) A small GTPase-related signal is fundamental for cellular function, anticipating that cerivastatin also causes cellular damage to other differentiating tissues. In fact, we examined the cytotoxic effect of statins on IM-9 lymphoblastic leukocytes in a more recent study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation